AKUNTABILITAS LAYANAN MASYARAKAT BERBASIS MEDIA DESA GUNA PENCEGAHAN KORUPSI - Zulkarnain Hamson; Hasnah Hasan; Nurul Mukhlishah; Asjulia Asjulia (Indonesian Collaboration Journal of Community Services (ICJCS), 2023)
Village, based on the general definition, is the agglomeration of settlements in rural areas (rural). Indonesia places villages in a government administrative area, under sub-districts, and is led by a village head. Law Number 22 Year 1999; Village is a legal community unit that has the authority to regulate and manage the interests of the local community based on local origins and customs. Village financing comes from the State Revenue and Expenditure Budget (APBN) transferred through the district / city Regional Revenue and Expenditure Budget (APBD), and is called the Village Fund. Indonesia Corruption Watch (ICW) recorded 46 cases of corruption in the village budget in 2019. After making observations, also Focus Group Discussions (FGD), interviews with village heads, listening to community information, it is deemed necessary to implement extension activities. For this reason, Community Service activities by a team of lecturers at the University of East Indonesia (UIT) in the hope that the village will be free from corruption